Legitimacy in Co‐Management: The Impact of Preexisting Structures, Social Networks and Governance Strategies. (28th December 2013) - Sandström, Annica; Crona, Beatrice; Bodin, Örjan
ABSTRACT With the ambition to contribute to the endeavour of co‐management, this paper focuses on the critical aspect of legitimacy and sets out to explain stakeholder acceptance in natural resource governance. A comparative study of five coastal and marine areas in Sweden is conducted. The empirical results demonstrate, first, how the past and the present institutional landscape set the underlying conditions and affect stakeholders' acceptance of new co‐management initiatives. Second, the results point to the critical function of network governance. Conscious choices regarding what composition of actors to involve, and in particular the inclusion and commitment of government actors, have significant bearing on stakeholder acceptance. Furthermore, deliberative efforts to reframe the process, adjusting the agenda to ongoing collaborative processes and key stakeholder goals, are seemingly as important. Thus, strivings towards legitimate co‐management require skilful manoeuvring of the present institutional landscape as well as deliberate strategies for the evolution of social networks. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment